Fields of study and graduates’ labour market outcomes in South Africa - Osunde, Sharon Wanbianoseh (University of the Witwatersrand, Johannesburg, 2023)
This study investigates job-education mismatch in South Africa based on graduates’ fields of study. Using data from the Quarterly Labour Force Survey for the period 2015 to 2019, we explore graduate endpoints in the labour market by determining how well-matched they are to their occupation and the association between being horizontally or vertically mismatched on earnings as well as job tenure. The results of the study found that Education and Health graduates are better matched to their occupations than Commerce and STEM graduates. Using a multinomial logistic regression to evaluate the likelihood of working in a match occupation, the study found that Commerce graduates are the most likely to transition into an occupation that they are overeducated for, while STEM graduates are more likely to transition into a horizontally mismatched occupation when compared to the other fields of study observed. Furthermore, using Mincerian OLS regressions, the study found a significant negative association between earnings and being overeducated among STEM and Commerce graduates. Lastly, this study also found a significant negative association between being horizontally mismatched and tenure among STEM and Commerce youth graduates
A Research Report submitted in partial fulfillment of the Degree of Master of Commerce Economic Science in the School of Economics and Finance, University of the Witwatersrand, 2023
Keywords: Job-education mismatch; Labour market; Education and Health graduates; UCTD; SDG-4: Quality education